(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: The Klebsiella pneumoniae (K. pneumoniae) is part of the healthy human microbiome, providing a potential reservoir for infection. It is most prevalent in healthcare settings and it is a significant nosocomial pathogen, leading to infections among hospitalized patients. Objective: To investigate the prevalence of multidrug resistance (MDR), extensively drug resistance (XDR) and pan-drug resistance (PDR) patterns among K. pneumoniae with their importance in mixed type isolates. Methods: This study is a cross-sectional investigation that included a total of 132 K. pneumoniae isolates, isolated from different infections collected from bacteriology laboratories located in six government hospitals in Baghdad. The Vitek2 system confirmed the bacterial and antibiotic susceptibilities. Results: The results showed that 106/132 (80.3%) of the isolates were pure K. pneumoniae, and 26/132 (19.7%) were mixed type isolates (K. pneumoniae plus other bacteria). It was found that the isolates were most resistant to beta-lactamase drugs and sulfonamide, such as Ticarcillin (97%), Piperacillin (92%), Ceftazidime (90%), Ticarcillin/Clavulanic acid (83%), Azatreonem (86%), and Trimethoprim/Sulfamethoxazole (86%). The antibiotic susceptibility patterns showed that 40/132 (30.3%) had possible XDR, 30/132 (22.7%) had MDR, and 16/132 (12.1%) had possible PDR. In the present study, burn infections followed by respiratory secretions revealed isolates with higher antibiotic resistance. Conclusion: The study revealed that high incidence of XDR and MDR patterns compared to previous studies conducted in Iraq in recent years. The co-existence of two or more bacterial species may lead to syntrophic interactions. The emergence of antibiotic-resistant strains among mixed strains has increased the severity of polymicrobial infection. Keywords: Klebsiella pneumoniae, antibiotics susceptibility patterns, poly-microbial infections. Citation: Fouad NA, Totl KJ. Antibiotic resistance in Klebsiella Pneumoniae and its impact in mixed type isolates. Iraqi JMS. 2024; 22(2): 369-376. doi: 10.22578/IJMS.22.2.22